Analisis Alih Fungsi Lahan Pertanian ke Non Pertanian di Desa Ajibarang Wetan, Kecamatan Ajibarang, Kabupaten Banyumas - Khanifudin, Khanifudin; , Drs. Suharjo, M.S; , Ir. Taryono, M. Si (2016)
Increasing need for land to people subsistence such as settlements, place of business (industry and services) and public facilities causes to increasing conversion of agricultural land to non-agricultural. This study aims to: (1) to identify the characteristic of demographic, social, and economic respondent, (2) analyze the factors affecting the level of interest agricultural land conversion in study areas, and (3) analize the distribution the level of interest agricultural land conversion in study areas This research location is in the village of Ajibarang Wetan, district Ajibarang, Banyumas. The location chosen because the development of district Ajibarang is in Ajibarang Wetan which causes the conversion of agricultural land. The method used in the research is census method from 50th respondent. Data analysis technique used descriptive analysis using frequency tables, cross tables, and statistical test product moment correlation of pearson. The results showed that farmers who owned land in the study area has the characteristics of elderly or dominated by the population aged > 60 years old and most have low education. Based on the statistical test product moment correlation, there are four factors which proven to have a correlation with the level of interest agricultural land conversion, this is land wide, land prices, land of social values, and perceptions of government policy on land conversion. Other factors such as the location of the land, obstacles in farming, and the compliance subsistence farmer is not proven to have a correlation with the level of interest agricultural land conversion. The level of interest agricultural land conversion in the study area is distributed fairly in "Dusun I" and "Dusun II" Keywords: Land, Farmer, land conversion, the level of interest farmer to agricultural land conversion